2014
DOI: 10.1007/s00464-014-3698-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous development of laparoscopy and robotics provides acceptable perioperative outcomes and shows robotics to have a faster learning curve and to be overall faster in rectal cancer surgery: analysis of novice MIS surgeon learning curves

Abstract: Initial robotic operative times improved with practice rapidly and eventually became faster than those for laparoscopy. Developing both laparoscopic and robotic skills simultaneously can provide acceptable perioperative outcomes in rectal surgery. It might be suggested that in the current milieu of clashing interests between evolving technology and economic constrains, there might be advantages in embracing both approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 27 publications
2
79
1
Order By: Relevance
“…Sixteen studies[10,12,14,16,17,22,23,25,27,28,37,38,40-42,48] (1257 patients) reported a totally robotic procedure which was carried out with either a single[10,16,17,22,23,25,27,28,37,38,40-42,48] or a double docking[12,28] technique. In 22 studies[8,13,15,18,20,21,25,26,30-34,36,39,43-47,49,50] (1384 patients) an hybrid robotic technique was performed: The inferior mesenteric vessels ligation and splenic flexure mobilization were performed laparoscopically whereas pelvic dissection and total mesorectal excision were performed robotically.…”
Section: Studies Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies[10,12,14,16,17,22,23,25,27,28,37,38,40-42,48] (1257 patients) reported a totally robotic procedure which was carried out with either a single[10,16,17,22,23,25,27,28,37,38,40-42,48] or a double docking[12,28] technique. In 22 studies[8,13,15,18,20,21,25,26,30-34,36,39,43-47,49,50] (1384 patients) an hybrid robotic technique was performed: The inferior mesenteric vessels ligation and splenic flexure mobilization were performed laparoscopically whereas pelvic dissection and total mesorectal excision were performed robotically.…”
Section: Studies Overviewmentioning
confidence: 99%
“…The mean value ranged from 17 mL[36] to 280 mL[14] with the robotic approach and from 59.2[18] to 271.4[15] in the laparoscopic group. Among 16 comparative studies[8-10,12-15,17,19-21,23,24,29,31,33] that evaluated the EBL only Kang et al[23] and Erguner et al[21] reported a significantly lower EBL with the robotic approach when compared to the laparoscopic one.…”
Section: Studies Overviewmentioning
confidence: 99%
“…The purported advantages of using a robot during surgery include improved depth perception, improved dexterity and control, and improved surgeon ergonomics [2]. The use of the technology allowing robot-assisted surgery was approved by the United States Food and Drug Administration (FDA) in 2000 [3].…”
mentioning
confidence: 99%
“…28 The intro of a learner in the MIS can be easier for the RRC than LRC in a specific center with rigorous protocols, which can be explained once more due to some of the structural advantages of the RS like the three-dimensional view, for instance. 29 But, acceptable outcomes can be fulfilled with simultaneously practical exercise.…”
Section: Discussionmentioning
confidence: 99%